Dampak PBL terhadap peningkatan keterampilan berpikir kritis pada materi pecahan - Indri Rahmawati; Mardiyana Mardiyana; Chumdari Chumdari (Curricula: Journal of Curriculum Development, 2026)
In mathematics learning in elementary schools. This study examines the effectiveness of the Problem-Based Learning (PBL) model in improving sixth-grade students' critical thinking skills in fractions in Sragen District during the 2025/2026 academic year. The background is students' low critical thinking skills, with an average score below the Kriteria Ketuntasan Minimal (KKM), as well as great difficulty in mathematical modeling and fraction operations. This study used a quantitative approach with a quasi-experimental design and cluster random sampling technique. The sample comprised 52 students in the experimental group (PBL model) and 54 in the control group (direct model). Data were collected through pretest and posttest instruments that had been tested for validity, reliability, discrimination power, and difficulty level. Data analysis was carried out using swimmer tests (normality and homogeneity) and ANOVA for hypothesis testing. The results showed that Fcount > Ftable, indicating a significant difference between the two groups. Thus, PBL is effective in improving critical thinking skills and encouraging active learning in elementary school students. The success of PBL implementation depends heavily on the quality of the problem design, the teacher's ability to facilitate the inquiry process, and students' readiness to engage in learning that demands independence and collaboration.